Synthesis and Characterization of Silver Nanoparticles With StarchâSodium Oleate and StarchâOleic Acid Inclusion Complexes as the Stabilizer - Alba, Santalum
Silver nanoparticles have good antibacterial capabilities, especially against gram-negative bacteria. In this research, silver nanoparticles should be stabilized by the inclusion complex of starch-oleic acid and starch-sodium oleate. In starches inclusion complex, oleic acid and sodium oleate wrapped into single helical amylose with non-covalent bonding. Beside for stabilizing, inclusion complex was expected to improve effectiveness of silver nanoparticles releasment. Inclusion complexes was made by mixing of starch solution ~ 1% (w/v) with each of oleic acid and sodium oleate were varied between 10-30% at 80-85 °C. Syntesis of silver nanoparticle was varied by heating time between 3 to 24 hours. Product of inclusion complexes was characterized using FT-IR spectroscopy and X-ray diffractometry (XRD). Then, inclusion complexes was mixed with AgNO3 and NaBH4 to forming silver nanoparticles. After that, silver nanoparticle was characterized using Particle Size Analyzer (PSA) and UV-Vis spectrophotometry. Beside that, Stability of silver nanoparticles was observed using UV-Vis spectrophotometry for 2 weeks. FT-IR spectrum show wavenumber shift of inclusion complex from 1712 cm-1 to 1706 cm-1 for the carbonyl group, 2925 cm-1 to 2922 cm-1 for alkanes, 3422 cm-1 to 3209 cm-1 for hydroxyl group, and appeared split peak at 990-994 cm-1. From diffractogram data, starch-inclusion complex of oleic acid and sodium oleate show V-6 type with orthorhombic structure. This was evidenced by formation of diffraction peak 2? = 13.070 and 19.300 on starch-oleic acid complex while starch-sodium oleate complex show diffraction peaks at 2? = 12,41o dan 19,450. UV-Vis spectrum of nanoparticle products show variety absorption peaks between 400-430 nm which indicate of silver nanoparticles. Otherwise, mixture of inclusion complex and AgNO3 without additional NaBH4 didn’t show absorption peak at UV-Vis spectrum area. In UV-Vis characterization, optimum concentration of AgNO3 in nanoparticles stabilized starches, inclusion complex starch-oleic acid, and starch-sodium oleate was 0.996 x 10-3 M, it means nanoparticle has small size and high concentration. Optimum size of silver nanoparticles stabilized starch-complex of oleic acid and sodium oleate respectively 31.1 ± 8.9 nm nm and 6.2 ± 1.5 nm. Stability test using UV-Vis was observed that silver nanoparticles with the addition of inclusion complex was relatively constant size, but concentration of silver nanoparticles relatively reduced since 4 weeks in storage.